Deadly decision in Beijing: Succession politics, protest repression, and the 1989 Tiananmen massacre - Su, Yang (New York Cambridge University press, 2023)
Three decades after 1989, historical materials are now available for understanding the Tiananmen protests in a new light. In a play-by-play account of the elite politics that led to the military crackdown, Su addresses the repression of the protest in the context of political leadership succession. He challenges conventional views that see the military intervention as a necessary measure against revolutionary mobilization.